2016
DOI: 10.1042/bcj20160066
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ferrichrome- and ferrioxamine B-mediated iron uptake by Aspergillus fumigatus

Abstract: Aspergillus fumigatus is an opportunistic fungal pathogen for immunocompromised patients, and genes involved in siderophore metabolism have been identified as virulence factors. Recently, we identified the membrane transporters sit1 and sit2, which are putative virulence factors of A. fumigatus; sit1 and sit2 are homologous to yeast Sit1, and sit1 and sit2 gene expression was up-regulated after iron depletion. When expressed heterologously in Saccharomyces cerevisiae, sit1 and sit2 were localized to the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…The significance of the low affinity iron transport has not been studied in details so far [ 29 , 30 ]. Both RIA and siderophore-mediated iron uptake are important in adaptation to iron starvation, however, only the contribution of siderophore biosynthesis and ferri-siderophore transport to virulence has been demonstrated until now [ 30 , 32 34 ]. The transcription factor HapX is crucial in regulating the iron starvation stress response in A. fumigatus [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the low affinity iron transport has not been studied in details so far [ 29 , 30 ]. Both RIA and siderophore-mediated iron uptake are important in adaptation to iron starvation, however, only the contribution of siderophore biosynthesis and ferri-siderophore transport to virulence has been demonstrated until now [ 30 , 32 34 ]. The transcription factor HapX is crucial in regulating the iron starvation stress response in A. fumigatus [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…No specific phenotype was observed for A. fumigatus Δ sit2 , however it has recently been shown that Sit2 is involved in ferrioxamine B uptake (Park et al, 2016). ImpC (AFUA_3G03670) is a putative ABC transporter and mRNA expression of ImpC is induced in response to iron-deplete conditions (Kragl et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In A. fumigatus, the SIDA gene that encodes the L-ornithine-N-monooxygenase is essential for siderophore production and contributes to virulence [75,147,152]. A. fumigatus also possess a highly conserved orthologs of the S. cerevisiae SIT1 and SIT2 transporter genes, and it was demonstrated that these transporters play a role in the uptake of ferrioxamine B and ferrichrome [153]. The deletion of the SID1 gene (ortholog of SIDA) in H. capsulatum, abolishes the siderophore biosynthesis pathway and inhibits fungal growth in bone marrow-derived macrophages and in mice.…”
Section: Siderophore Uptakementioning
confidence: 99%